Pendampingan Penyusunan Perangkat Pembelajaran Daring dan Luring Bagi Mahasiswa Fakultas Tarbiyah dan Ilmu Keguruan Universitas Islam Negeri Imam Bonjol Padang - Adriantoni Adriantoni (Jurnal Dedikasia : Jurnal Pengabdian Masyarakat, 2022)
This service activity aims to equip primary teacher education students who will carry out practical field experience in schools and madrasas on how to compose and develop online and offline learning tools. The ability to develop learning tools is a very important thing that must be mastered by prospective teachers. This mentoring activity method is carried out online using the zoom application with 80 participants. The approach used is the lecture method, meaning that the material is explained first and then followed by a question and answer session. The result of this mentoring activity is that there are still student teacher candidates who will carry out practical field experience who have not been able to develop and develop learning tools, especially developing the latest single sheet lesson plan. Based on the results of these mentoring activities, it can be concluded that: there are still some practical field experience students who do not know the latest policies regarding the use of one-sheet lesson plans in schools and are still unable to prepare lesson plans properly and correctly according to the standard of the learning process. From these conclusions, the authors recommend: to prospective practical field experience students to improve literacy before going to school and to Lecturers who are in charge of Learning Planning courses in conducting comprehensive evaluations